Increased nitrogen cycling facilitates native forest regeneration: Potential for restoring extinct ecological processes?. Issue 1 (1st January 2013) - Tanentzap, Andrew J.; Lee, William G.; Monks, Adrian
Abstract : Ecological processes often maintain the plant communities with which they have a long evolutionary association, and so their loss may favor invasions by nonnative species. We simulated the effects of fecal deposition and soil turnover by the extinct avian megafauna of New Zealand to test their influence on woody plant regeneration and nonnative plant invasion in a cool temperate rain forest. Hen manure increased soil available NO3 −, leading to greater seedling regeneration relative to control plots. Although soil P was elevated within plots treated with hen manure, concentrations also increased within plots treated with liquid fertilizer, which did not have different seedling densities relative to controls. Simulated avian soil disturbance did not increase seedling densities, and none of the three treatments affected the proportion of woody seedlings that were nonnative. However, pretreatment variation in NO3 − availability, which reflected longer‐term rates of nitrogen cycling, reduced community invasibility. Our findings suggest that avian‐derived nitrogen inputs increase the regeneration of native forests, raising the question of whether the functional role of extinct megaherbivores is absent in New Zealand.